1990
DOI: 10.1002/1097-0142(19901001)66:7<1461::aid-cncr2820660704>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of patients with isolated axillary nodal metastases from an occult primary carcinoma consistent with breast origin

Abstract: The records of 42 patients who had axillary metastases compatible with a clinically occult breast primary were reviewed. Forty patients had mammography performed as part of their evaluations. Mastectomy yielded the primary tumor in one of 13 patients; biopsy yielded positive results in one of five. Among the 29 patients who did not undergo mastectomy, 16 received breast irradiation, and 13 were simply observed for signs of the primary tumor. For the patients who did not undergo mastectomy, the 5-year actuarial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0
7

Year Published

1993
1993
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(59 citation statements)
references
References 16 publications
2
50
0
7
Order By: Relevance
“…It should be reminded that seven of 10 CUPAx patients would be found to harbour a small breast primary on mastectomy. Moreover, in three series a trend for survival advantage in CUPAx patients receiving adjuvant therapy was suspected [17,18,28] despite frequent lack of adequate management of the breast/axilla fully eradicating gross disease. No series provide information on use of neoadjuvant chemotherapy in patients with CUPAx: most patients undergo axillary nodal clearance immediately after fine needle aspiration/ excisional biopsy or in the presence of unresectable lymph nodes, axillary irradiation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be reminded that seven of 10 CUPAx patients would be found to harbour a small breast primary on mastectomy. Moreover, in three series a trend for survival advantage in CUPAx patients receiving adjuvant therapy was suspected [17,18,28] despite frequent lack of adequate management of the breast/axilla fully eradicating gross disease. No series provide information on use of neoadjuvant chemotherapy in patients with CUPAx: most patients undergo axillary nodal clearance immediately after fine needle aspiration/ excisional biopsy or in the presence of unresectable lymph nodes, axillary irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical significance of these survival differences was reached occasionally. In 1990 Ellerbroek et al [17] presented a series of 42 patients of whom 13 were treated with mastectomy, 16 with breast irradiation and 13 observed. They reported that breast cancer-free 5-year survival was 83% for patients who had their breasts conserved but treated with irradiation versus 43% for those who were managed with observation (P = 0.06).…”
Section: Observation Versus Local Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Other treatment-responsive subgroups have been described with characteristic clinicopathological presentations, including women with adenocarcinoma involving axillary lymph nodes 16,17) and patients with squamous cell carcinoma involving cervical lymph nodes. 18) In this study, however, there was no patient belonging to either of these subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…A breast cancer is usually presumed when a women presents with adenocarcinoma in the axillary nodes without an evident primary [39][40][41][42][43][44]. MRI has been particularly helpful when there is a high suspicion of a breast primary with a negative physical exam and mammogram [43,44].…”
Section: David M Mintzer Mdmentioning
confidence: 99%